PETROGRAPHIC FEATURES OF SEGMENT II OF THE JINCHUAN INTRUSION, GANSU, AND ITS FRACTIONAL CRYSTALLIZATION - Li S.B.; Song X.Y.; Hu R.Z.; Chen L.M.; Nie X.Y. (My University, 2007)
Segment II of the Jinchuan intrusion is composed mainly of lherzolite and sulfide peridotite. Fine- and medium-grained harzburgite occurs as a "roof pendant" at the top of the intrusion and shows a short-distance gradational relationship with the medium-grained lherzolite, reflecting the feature of multiple injections of magma or "crystal mush". Based on the petrographic relationships between the minerals of various rock facies, combined an analysis of the thermodynamics phase diagrams, the authors think that the crystallization sequence of the rock-forming minerals in Segment II is spinel, olivine, orthopyroxene, clinoyroxene and plagioclase. Reaction between olivine and parent magma caused olivine crystals to become rounded. In addition, the grain size of cumulus olivine in the sulfide peridotite and sulfide harzburgite is obviously smaller than that of olivine in the sulfide lherzolite, implying that abundant sulfide ore pulp had gathered at the bottom of the deep magma chamber before the "crystal mush" was intruded into the shallow magma chamber.
Keywords: FRACTIONAL CRYSTALLIZATION; JINCHUAN CU-NI SULFIDE DEPOSIT; PETROGRAPHIC FEATURES; PHASE DIAGRAM; SEGMENT II